Systematic Review: Factors Associated with the Incidence of Colorectal Cancer - Tassya Alfiola; Ummi Kalsum; Fairuz Quzwain (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Colorectal carcinoma (CRC) ranks third in global cancer incidence with an estimated 1.93 million new cases in 2020 and constitutes the second leading cause of cancer-related mortality worldwide. Indonesia documented 34,189 new cases, predominantly diagnosed at advanced stages, underscoring the critical need for comprehensive identification of CRC risk determinants. Objective: To systematically synthesize factors associated with CRC occurrence and analyze the magnitude of their associations to formulate evidence-based prevention recommendations. Methods: A systematic literature review following PRISMA 2020 guidelines was conducted across PubMed, Google Scholar, and ScienceDirect (2015–2024), yielding 30 selected articles from 309 initial records. Results and Discussion: Non-modifiable factors demonstrated the highest associations, including first-degree family history (OR 17.78), precancerous lesions (OR 8.57), and inflammatory bowel disease (OR 7.07). Modifiable factors encompassed physical inactivity (OR 5.69), excessive red meat consumption (OR 4.97), alcohol (OR 4.92), central obesity causally confirmed via Mendelian randomization (OR 1.38), diabetes (HR 2.20), and hypertension (HR 1.99). Gut microbiota dysbiosis actively contributed to carcinogenesis through genotoxicity and chronic inflammation mechanisms. Conclusion: CRC is multifactorial in nature; while non-modifiable factors carry larger absolute effect sizes, modifiable factors offer more strategically actionable intervention targets